Exome-wide Rare Variant Analysis Identifies TUBA4A Mutations Associated with Familial ALS - Smith, Bradley N.; Ticozzi, Nicola; Fallini, Claudia; Gkazi, Athina Soragia; Topp, Simon; Kenna, Kevin P.; Scotter, Emma L.; Kost, Jason; Keagle, Pamela; Miller, Jack W.; Calini, Daniela; Vance, Caroline; et al. (Neuron (Cambridge, Mass.), 2014)
Exome sequencing is an effective strategy for identifying human disease genes. However, this methodology is difficult in late-onset diseases where limited availability of DNA from informative family members prohibits comprehensive segregation analysis. To overcome this limitation, we performed an exome-wide rare variant burden analysis of 363 index cases with familial ALS (FALS). The results revealed an excess of patient variants within TUBA4A, the gene encoding the Tubulin, Alpha 4A protein. Analysis of a further 272 FALS cases and 5,510 internal controls confirmed the overrepresentation as statistically significant and replicable. Functional analyses revealed that TUBA4A mutants destabilize the microtubule network, diminishing its repolymerization capability. These results further emphasize the role of cytoskeletal defects in ALS and demonstrate the power of gene-based rare variant analyses in situations where causal genes cannot be identified through traditional segregation analysis. [Display omitted] •Mutations in tubulin, alpha 4A (TUBA4A) are associated with familial ALS•TUBA4A mutants act as dominant negatives to alter microtubule dynamics and stability•Results provide further evidence supporting a role of cytoskeletal defects in ALS•Rare variant analysis of index familial cases can identify human disease genes Smith et al. show that alterations in the Tubulin, Alpha 4A gene, which encodes a cytoskeletal protein, contribute to the pathogenesis of familial ALS. This Report provides further evidence supporting a major role of cytoskeletal defects in ALS.